Evaluating the Effect of Lymph Node Status on Survival in Large Colon Cancer - Liu, Qi; Luo, Dakui; Li, Qingguo; Zhu, Ji; Li, Xinxiang (Frontiers in Oncology, 2018)
Objective: This study aimed to investigate the effect of lymph node status on survival in large colon cancer. Methods: In the first cohort, patients diagnosed with non-metastatic colon cancer (N = 176,834) were identified from the Surveillance, Epidemiology, and End Results (SEER) database between January 1988 and December 2005. Further analyses were conducted in the other cohort (N = 855) from the Fudan University Shanghai Cancer Center (FUSCC) database. Results: In the SEER cohort, CSS differences increased as the tumor enlarged until a threshold tumor size group (tumor measuring 7–8 cm, P < 0.001) was reached, in which node positivity showed the maximum negative effect on CSS; multivariate Cox analyses showed that tumors measuring 7–8 cm presented a significant lower risk of cancer-specific mortality compared with those measuring 2–4 cm [hazard ratio (HR) = 1.087; 95% confidence interval (CI) = 1.014–1.165, P = 0.018]. In the FUSCC cohort, N0 tumors measuring 21–40 mm presented a higher risk of recurrence compared with those measuring 41–80 mm. Conclusions: Mortality risk of node positivity increased as tumor enlarged until a threshold tumor size (tumor size of 7–8 cm) was reached, mainly resulting from larger tumors without lymph node involvement being a surrogate for biologically indolent colon cancer of tumor recurrence. Our study could provide both researchers and clinicians a better understanding of colon cancer biology.